Da descrição ao ensino da oração adjetiva: a perspectiva dos livros didáticos de língua portuguesa - Pezatti, Erotilde Goreti [UNESP]; Câmara, Aliana Lopes [UNESP] (My University, 2014)
This paper aims at investigating the treatment given to relative clauses by elementary school text books, evidencing how the teaching of grammar is proposed in the teacher’s books. As a consequence, this study also intends to discuss important aspects to be considered as far as the teaching of relative clauses is concerned. In order to achieve that objective, five Portuguese text books (approved by the Programa Nacional do Livro Didático-2014) were selected so that the grammar teaching proposals could be analyzed in relation to the definition and to the distinguishing criteria between defining and non-defining relative clauses. Results show that the teaching of relative clauses (as proposed by the teacher’s books) still reflects the postulates of the traditional grammar, based on activities of identification and classification of morphosyntactic units, ignoring the pragmatic and prosodic aspects.

O objetivo deste trabalho é analisar o tratamento dado à oração adjetiva pelos livros didáticos do nível fundamental, verificando como é implementada a proposta de ensino de gramática contida nos manuais do professor. Como consequência, pretende-se também relacionar alguns aspectos importantes a serem considerados no ensino da oração adjetiva. Para isso, foram selecionados cinco livros didáticos aprovados no Programa Nacional do Livro Didático-2014, que serviram de base para a análise da proposta de ensino, referente aos critérios de definição e de distinção entre oração adjetiva restritiva e explicativa. Os resultados mostram que o ensino de oração adjetiva ainda reflete os postulados da gramática tradicional e se baseia em atividades de identificação e classificação das unidades morfossintáticas, desconsiderando aspectos pragmáticos e prosódicos.
From description to teaching of relative clauses: the perspective of text books in portuguese
Keywords: Ensino; livro didático; orações adjetivas; funcionalismo; grammar teaching; relative clause; functionalism; text book